Aplikasi lampu bertenaga surya untuk penerangan - Abdus Shomad; Sutoyo; Zuhri Nurisna; Son Ali Akbar (Jurnal Dedikasi Masyarakat, 2023)
Electricity use tends to come from energy produced by PLN, where the energy produced in several areas is from non-renewable oil-fueled power plants. This causes several areas to remain dark because they do not have street lighting and are dependent on electricity services from the government, including Banguntapan Village which has minimal lighting. The absence of lighting makes the road dark and prone to crime such as theft, which is often due to darkness. To prevent theft, residents are required to guard the village system, but this is not optimal. For this reason, community service is carried out by creating a sense of security through the street lighting construction program in Banguntapan Village, especially the Muhammadiyah Islamic Center (MIC) complex. The aim of carrying out this community service activity is to provide an alternative, renewable electrical energy source by utilizing solar panels that the community can use. Activities were carried out in several stages, namely observation, outreach, and counseling, as well as training on solar-powered lighting installations. The activity partner is PRM 3 Banguntapan which is located in the Muhammadiyah Islamic Center (MIC) complex, precisely in Sorowajan Hamlet, Banguntapan Village. The results obtained are the availability of alternative electrical energy sourced from sunlight stored in batteries and solar-powered lighting units. Residents know and understand that the use of solar energy is a form of energy-independent village development.